Adult Hippocampal Neurogenesis: Regulation and Possible Functional and Clinical Correlates - Baptista, Pedro; Andrade, José P. (Frontiers in Neuroanatomy, 2018)
The formation of new neurons in the adult central nervous system (CNS) has been recognized as one of the major findings in neuroanatomical research. The hippocampal formation (HF), one of the main targets of these investigations, holds a neurogenic niche widely recognized among several mammalian species and whose existence in the human brain has sparked controversy and extensive debate. Many cellular features from this region emphasize that hippocampal neurogenesis suffers changes with normal aging and, among regulatory factors, physical exercise and chronic stress provoke opposite effects on cell proliferation, maturation and survival. Considering the numerous functions attributable to the HF, increasing or decreasing the integration of new neurons in the delicate neuronal network might be significant for modulation of cognition and emotion. The role that immature and mature adult-born neurons play in this circuitry is still mostly unknown but it could prove fundamental to understand hippocampal-dependent cognitive processes, the pathophysiology of depression, and the therapeutic effects of antidepressant medication in modulating behavior and mental health.